Activated Carbon Coconut Shell as Base of Anode Battery: A Review - Erwan Adi Saputro; Sukirmiyad; Susilowati; Silvana Dwi Nurherdiana; Diana Silvia Rahma Wardhani; Kirana Aurelia Salshabila; Nurten Sahan (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Presently, there is a rapid and significant advancement in battery technology. Consequently, there is a concurrent rise in the demand for energy to fulfil every day, industrial, and transportation requirements. A promising avenue for diminishing reliance on non-renewable energy sources is the innovative conversion of waste materials into alternative energy reservoirs. In this context, the conversion of discarded coconut shells into activated carbon emerges as a valuable strategy for fabricating battery anodes. Several constituents, including activated carbon, LiOH, TiO2, and adhesives, can be employed in the production of battery anodes. The amalgamation of activated carbon with LiOH yields an electrical conductivity of 2.064 x 10-3 Sm-1, along with a specific capacitance of 4.46154 F/g for activated carbon derived from coconut shells. Alternatively, other carbon composites exhibit superior electrical conductivity, registering a value of 15.31 x 10-2 Sm-1, accompanied by a specific capacitance of 140.2 F/g. This comprehensive literature review aims to serve as a pivotal resource for selecting optimal raw materials in the synthesis of battery anodes. The result of this review substantiates that activated carbon sourced from coconut shells is one of favourable materials for crafting battery anodes.